2019
DOI: 10.1177/1934578x19850374
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Acidic Polysaccharide From Schisandra chinensis in STZ-Induced Diabetic Mice

Abstract: Polysaccharide, one of the main components in Schisandra chinensis, has been discovered to have an antidiabetic effect. In this study, we further observed the effect of the secondary component of Schisandra polysaccharide, acidic polysaccharide, on diabetes induced by streptozotocin (STZ) in mice and H 2 O 2 -induced MIN6 cell injury model and investigated the underlying mechanisms at the same time. The results showed that S. chinensis acidic polysaccharide (SCAP) could increase the content of fasting blood in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…S. Chinensis polysaccharide (SCAP) has a therapeutic impact on streptozotocin (STZ) and this protective influence maybe mediated via preventing the apoptosis of β-cells by inhibiting the expression of phosphor C-Jun N-terminal kinase (JNK) and related apoptotic proteins. 81 Modern pharmacological research has demonstrated that most of the biological actions and pharmacological effects of Wuweizi can be attributed to its lignan constituents, particularly the dibenzocyclooctadiene-type lignans, which can lower the serum glutamate-pyruvate transaminase (SGPT) level, inhibit platelet aggregation and show antioxidative, calcium antagonism, antitumor-promoting and anti-HIV (human immunodeficiency virus) effects. 82 Rybnikar et al 83 found that their activity has been investigated in hundreds of studies that have confirmed adaptogenic effects, central nervous system stimulation, hepatoprotective effects and potential anticancer potential.…”
Section: Modern Pharmaceutical Sciencementioning
confidence: 99%
“…S. Chinensis polysaccharide (SCAP) has a therapeutic impact on streptozotocin (STZ) and this protective influence maybe mediated via preventing the apoptosis of β-cells by inhibiting the expression of phosphor C-Jun N-terminal kinase (JNK) and related apoptotic proteins. 81 Modern pharmacological research has demonstrated that most of the biological actions and pharmacological effects of Wuweizi can be attributed to its lignan constituents, particularly the dibenzocyclooctadiene-type lignans, which can lower the serum glutamate-pyruvate transaminase (SGPT) level, inhibit platelet aggregation and show antioxidative, calcium antagonism, antitumor-promoting and anti-HIV (human immunodeficiency virus) effects. 82 Rybnikar et al 83 found that their activity has been investigated in hundreds of studies that have confirmed adaptogenic effects, central nervous system stimulation, hepatoprotective effects and potential anticancer potential.…”
Section: Modern Pharmaceutical Sciencementioning
confidence: 99%
“…This polysaccharide also prevented apoptosis of pancreatic β-cells through the up-regulation of factors such as BAX and Bcl-2, suggesting a possible mechanism for its antidiabetic activity. [ 75 ].…”
Section: Metabolic Syndrome and Cardiovascular Riskmentioning
confidence: 99%